The molecular mechanism of leaf margin fission in Solanum nigrum revealed by combined PPI network and WGCNA and functional validation of SnNAC90 - Shen, Hongquan; Miao, Man; Cha, Zhoumin; Fan, Zexi; Cai, Qihang; Sun, Zhenghai; Li, Liping (Frontiers in Plant Science, 2025)
IntroductionSolanum nigrum, a member of the Solanaceae family, holds significant importance in various aspects, including edible and medicinal uses, ecological management, and environmental landscaping. The leaf edges of S. nigrum exhibit 4–5 significant serrations, and the splitting of these leaf margins plays a crucial role in the plant’s adaptation to environmental shifts.MethodsIn this study, we systematically analyzed the molecular mechanism of leaf margin fission in S. nigrum by combining RNA sequencing, weighted gene co-expression network analysis, and overexpression transgenic technology using leaves from five growth stages of S. nigrum during the flowering period as materials.ResultsTranscriptome analysis revealed that 30,311 differentially expressed genes were activated from leaf bud to mature leaf, and these genes were significantly enriched in metabolic pathways related to signal transduction and glycosynthesis. Differential genes were hierarchically clustered into 13 modules. The correlations of these modules with different growth stages of S. nigrum leaves, as well as the number and depth of leaf notches were analyzed. It was found that the turquoise expression module (ME1) was significantly and positively correlated with the leaf bud stage (r = 0.94, p < 0.01), while negatively correlated with the number and depth of leaf notches. Three highly connected hub genes were identified from network interactions analysis of genes related to the leaf differentiation pathway in Module 1. From the intersection of the turquoise module and the 2 clusters screened by temporal analysis, the core gene (SnNAC90) for leaf margin fission in lobelia was identified. The regulatory role of the SnNAC90 gene in tobacco leaves was preliminarily verified by transgenic technology.DiscussionIt was hypothesized that it might positively regulate leaf margin fission in S. nigrum. Preliminary speculation on its regulatory role in S. nigrum leaves. This study, for the first time, revealed the regulatory mechanism of leaf margin division in S. nigrum, providing a theoretical basis for enriching its germplasm resources and serving as a reference basis for cultivating leaf plants.